Nutritional and Quality Characteristics of Some Foods Fortified with Dried Mushroom Powder as a Source of Vitamin D - Rehab Mohamed Ibrahim; Maha IK Ali; Faten Farouk Abdel-salam (International Journal of Food Science)
Vitamin D plays a vital role in synthesizing calcium-carrying proteins in the small intestine and helps the absorption of calcium in the body, thus reducing the risk of rickets in children and osteoporosis in adults, especially in women. So, the objective of this study was to evaluate the nutritional value and quality characteristics of some food products such as waffles, breadsticks and salad cream fortified with dried mushroom powder (DMP) after exposure to sunlight for 60 min as a source of vitamin D. The exposure of mushroom to sunlight for 60 min before drying increased its content of vitamin D by 158% more than fresh mushroom (not exposed to sunlight). The DMP was added to the product’s formula by a ratio of 1, 2, and 3%. The addition of DMP increased protein, ash, fat, and vitamin D2 and D3 contents in all products, while carbohydrates and moisture contents were decreased in both waffles, and breadsticks. The hardness of both waffles and breadsticks was decreased with increasing the levels of DMP added, while the addition of DMP led to enhance bioactive compounds and antioxidant activity in all products. The sensory evaluation of waffles, breadsticks, and salad cream containing DMP was not changed than control sample. The results found that the intake of 100 g of salad cream, waffles, and breadstick (containing 3% DMP) could by providing more than the recommended daily allowances (RDA) of vitamin D. Therefore, this study recommended the use of DMP (by a ratio of 3%) in fortifying food products in order to meet the RDA of vitamin D.